Variable selection in nonparametric functional concurrent regression. Issue 1 (24th September 2021) - Ghosal, Rahul; Maity, Arnab
Abstract : We develop a new method for variable selection in nonparametric functional concurrent regression. The commonly used functional linear concurrent model (FLCM) is far too restrictive in assuming linearity of the covariate effects, which is not necessarily true in many real‐world applications. The nonparametric functional concurrent model (NPFCM), on the other hand, is much more flexible and can capture complex dynamic relationships present between the response and the covariates. We extend the classically used variable selection methods, e.g., group LASSO, group SCAD and group MCP, to perform variable selection in NPFCM. We show via numerical simulations that the proposed variable selection method with the non‐convex penalties can identify the true functional predictors with minimal false‐positive rate and negligible false‐negative rate. The proposed method also provides better out‐of‐sample prediction accuracy compared to the FLCM in the presence of nonlinear effects of the functional predictors. The proposed method's application is demonstrated by identifying the influential predictor variables in two real data studies: a dietary calcium absorption study, and some bike‐sharing data. Résumé : Cet article propose une nouvelle méthode de sélection de variables dans un contexte de modèles concurrents fonctionnels non paramétriques. Comme l'hypothèse de linéarité des effets des covariables qu'impose un modèle concurrent fonctionnel linéaire usuel soit trop restrictive pour que ce dernier soit valide et utile dans des applications réelles, les auteurs de ce travail ont opté pour des modèles fonctionnels concurrents non paramétriques (NPFCM). Ces modèles sont bien plus souples et capables de capturer les relations dynamiques complexes liant une variable réponse et ses covariables. Ils ont, donc, repris des méthodes de sélection de variables classiques, telles: LASSO, SCAD et MCP de groupes pour les étendre aux modèles de type NPFCM. Des simulations numérqiues montrent clairement que la méthode proposée avec les pénalités non convexes peut identifier les véritables prédicteurs fonctionnels avec un taux de faux positifs minimal et un taux de faux négatifs négligeable. Aussi, en présence d'effets non linéaires des prédicteurs fonctionnels, elle fournit une meilleure précision de prédiction hors échantillon comparativement à celle d'un modèle concurent fonctionnel linéaire. En guise d'illustration pratique, la méthode proposée a été appliquée à deux jeux de données, l'un portant sur l'absorption de calcium alimentaire et l'autre sur un système de partage de vélos.